2011
DOI: 10.1177/0022034511405322
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal Progenitors and Dentin Repair

Abstract: Mesenchymal stem cells are present in the dental pulp. They have been shown to contribute to dentin-like tissue formation in vitro and to participate in bone repair after a mandibular lesion. However, their capacity to contribute efficiently to reparative dentin formation after pulp lesion has never been explored. After pulp exposure, we have identified proliferative cells within 3 zones. In the crown, zone I is near the cavity, and zone II corresponds to the isthmus between the mesial and central pulp. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
(20 reference statements)
1
29
0
Order By: Relevance
“…Indirect data from BrdU labeling experiments have brought support to this hypothesis (Ishikawa et al, 2010;Téclès et al, 2005). But the fact that DPSCs appear as a heterogeneous cell population raises the question of the existence of other potential stem cell niches in the pulp (Harichane et al, 2011;Mitsiadis et al, 1999Mitsiadis et al, , 2003 Table 3. Different types of stem cells from the tooth: isolation, culture procedures and differentiation potentials Working with stem cells requires their growth and expansion in vitro.…”
Section: Maintenance Of Cell Potentialities In Vitromentioning
confidence: 99%
“…Indirect data from BrdU labeling experiments have brought support to this hypothesis (Ishikawa et al, 2010;Téclès et al, 2005). But the fact that DPSCs appear as a heterogeneous cell population raises the question of the existence of other potential stem cell niches in the pulp (Harichane et al, 2011;Mitsiadis et al, 1999Mitsiadis et al, , 2003 Table 3. Different types of stem cells from the tooth: isolation, culture procedures and differentiation potentials Working with stem cells requires their growth and expansion in vitro.…”
Section: Maintenance Of Cell Potentialities In Vitromentioning
confidence: 99%
“…If a pulse of the thymidine analog BrdU is given to young animals at the optimal time, slow-cycling long-term label-retaining cells (LRCs), putative stem/progenitor cells, can be seen scattered among unlabeled or lightly labeled cells, presumably transit amplifying cells, in the tissue even after a period of several weeks (Morris et al 2004;Yue et al 2005), although hematopoietic stem cells cannot be identified on the basis of BrdU-label retention as demonstrated by a previous paper (Kiel et al 2007). However, the dental pulp stem cells rarely proliferate in the matured tissue under the normal condition and they are induced to leave their quiescent stage in response to tooth injuries to actively proliferate under the pathological conditions, such as cavity preparation, pulp exposure and tooth replantation/transplantation (Harada et al 2008;Harichane et al 2011;Hasegawa et al 2007;Kuratate et al 2008;Ogawa et al 2006;Takamori et al 2008;Unno et al 2009), since the dental pulp is not a continuously renewing tissue such as epidermis. Our recent study has demonstrated that five intraperitoneal injections of BrdU (E17-21) into pregnant Wistar rats (pregnant labeling method) enable the successful identification of dense LRCs, presumably adult stem/progenitor cells, in the mature tissue of postnatal animals and that putative adult stem/progenitor cells mainly reside in the center of the dental pulp, associating with blood vessels (Ishikawa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect data from BrdU labeling experiments have brought support to this hypothesis (Ishikawa et al, 2010;Téclès et al, 2005). But the fact that DPSCs appear as a heterogeneous cell population raises the question of the existence of other potential stem cell niches in the pulp (Harichane et al, 2011;Mitsiadis et al, 1999Mitsiadis et al, , 2003. Table 3.…”
Section: Maintenance Of Cell Potentialities In Vitromentioning
confidence: 99%